Unilateral Gingival Fibromatosis: a case report - Patussi, Cleverson; Ramos, Caroline Beatrice; Sassi, Laurindo Moacir; Pedruzzi, Paola Andréia G.; Ramos, Gyl Henrique Albrecht (Brazilian Dental Science, 2014)
The gingival fibromatosis is a slow and progressive benign proliferation, which affects the gingival tissues. It may present a genetic inheritance and association with some syndromes. There are conservative and radical treatments, ranging from hygiene care to bloc resection of the affected bone. This case scenario is a 07 year-old child, who presented a nodular unilateral hyperplastic lesion in the right mandible, with sessile base and approximately 5 cm in its largest diameter. The patient presented difficulty of lip closure and slight swelling in the right area of the face. The tomographic image showed infiltration in buccal and lingual cortical of right mandible and tooth displacement. After lesion removal, the histopathologic diagnosis of fibromatosis was confirmed, with no relapse after 20 months of follow-up.